1981
DOI: 10.3758/bf03326956
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative avoidance learning in hippocampal and cortical rats: Acquisition rate, behavioral strategies, and long-term retention

Abstract: Facilitation of visually discriminated avoidance learning was observed in rats 1 week after they were lesioned in the dorsal hippocampus. While perseveration of a spatial strategy acquired during a pretraining session occurs in sham-operated and cortically lesioned controls, no such perseveration was observed in hippocampals. Elimination of the presurgical shaping session reduced the number of spatial strategies in all groups, but differences in trials to criterion and percentage of place strategies remained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1981
1981
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
(29 reference statements)
0
6
1
Order By: Relevance
“…results has been reported in hippocampal-lesioned rodents tested on a visual discrimination (Sara & David-Remacle, 1981) and a passive avoidance (Zornetzer et al, 1977) habit. ]…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…results has been reported in hippocampal-lesioned rodents tested on a visual discrimination (Sara & David-Remacle, 1981) and a passive avoidance (Zornetzer et al, 1977) habit. ]…”
mentioning
confidence: 66%
“…Sara and David-Remacle (1981) have reported that hippocampal-lesioned rats show defective retention of a visual discrimination habit without showing defective learning. A similar pattern of results has been reported by Zornetzer, Gold, and Boast (1977) in connection with learning and retention of a passive avoidance task in hippocampal-lesioned mice.…”
mentioning
confidence: 99%
“…The dissociation between the acquisition and retention of object discriminations demonstrated by angular bundle animals stands in contrast to the more global deficits seen in rats with hippocampal damage on traditional spatial measures of memory. For example, rats with hippocampal lesions are impaired on both the acquisition and long-term retention of spatial information (Sara and David-Remacle, 1981;Peinado-Manzano, 1990). That hippocampal lesions lead to both acquisition and retention impairments on measures of spatial memory likely reflects the declarative nature of this information (Squire, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Such a facilitative effect has recently been observed by Sara and David-Remacle (1981) in hippocampally lesioned rats and by Thompson (1982a) in mammillary-body-lesioned rats . The present study disclosed that anterior-thalamic-lesioned rats learn a white-black discrimination problem faster than do controls.…”
Section: General Findingsmentioning
confidence: 86%